Score for Neonatal Acute Physiological Evaluation with Perinatal Extension (SNAPPE II) as a predictor of mortality from neonatal sepsis - Quispe Castañeda, Claudia Vanessa; Becerra-Villanueva, Luis Alonso; Alva-Vargas, Marcela Sofía; Meregildo-Rodríguez, Edinson Dante; Vásquez-Tirado, Gustavo Adolfo (Paediatrica Indonesiana, 2025)
Background Sepsis is considered one of the leading causes of neonatal mortality. In the quest to reduce neonatal mortality, it is crucial to identify factors that increase the risk of death in neonates. The use of tools such as assessment scales allows us to identify neonates at higher risk of mortality. The SNAPPE II scale might be a predictive factor for mortality in this age group, could be considered as a tool to be used in all neonatal ICU (NICU). Objective To determine whether SNAPPE II, with a score of ? 40 points, is a good predictor of mortality due to neonatal sepsis. Methods A retrospective cohort study was conducted on 162 term neonates diagnosed with neonatal sepsis at the Víctor Lazarte Echegaray Hospital, within the neonatal intermediate care unit (NIMCU) and NICU, from 2021 to 2023. The SNAPPE II scale was applied to all subjects, and scores were analyzed for potential associations with subject mortality. Results The SNAPPE II score was associated with mortality in neonatal sepsis. Multivariable logistic regression analysis revealed a significant association at cut-off of ? 40 pints between higher score and subject mortality (aOR=1.29; 95%CI 1.13 to 1.56; P<0.001). Additionally, we found that mechanical ventilation was an independent predictor of mortality from neonatal sepsis (aOR=1.48; 95%CI 1.46 to 151.9; P<0.01). Conclusion The SNAPPE II score with a cut-off of 40 points is a good predictor of mortality in neonatal sepsis.